Microstrip Antenna Design for a non-Invasive Glucose Sensor - Baharuddin, Merna; Dewiani, Dewiani; Rayhana, Mutiah; Syarif, Syafruddin; Palantei, Elyas (Faculty of Engineering, Andi Djemma University, 2022)
Diabetes Mellitus (DM) is one of the diseases with many patients in the world. The current method used by people with diabetes was an invasive approach using blood samples to monitor their blood glucose levels. The non-invasive approach that does not require blood samples would increase ease-of-use for diabetics. This research presents a microstrip antenna to monitor glucose levels in human blood non-invasively. The background concept of this approach was blood glucose variation causes variations of blood permittivity accordingly. This blood permittivity will affect the resonant frequency of the microstrip antenna. Antenna design and simulation were performed using CST Microwave Studio software. The antenna is designed on FR4 (εr = 4.3) dan NPC H220 (εr = 2.17) substrate with h = 1.6mm. A patch of microstrip antenna placed on one side and ground plane on another side, they are connected using SMA connector. The fabrication result of the designed antenna has an operating frequency of 2.17 GHz. In this research, the correlation between blood glucose and changing the microstrip antenna’s resonant frequency was observed. For this non- invasive method, the microstrip antenna is placed facing the forearm. Experimental results of both approaches, antenna placement with and without spacing to the forearm, show the shift of resonant frequency according to blood glucose changes. Based on this research’s linearity, accuracy, and sensitivity result, the microstrip antenna shows potential as a glucose- sensing device for a non-invasive method with further development.